2021
DOI: 10.3389/fimmu.2021.638381
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Nox2 Plays a Key Role in the Pathogenesis of Experimental Autoimmune Encephalomyelitis

Abstract: While oxidative stress has been linked to multiple sclerosis (MS), the role of superoxide-producing phagocyte NADPH oxidase (Nox2) in central nervous system (CNS) pathogenesis remains unclear. This study investigates the impact of Nox2 gene ablation on pro- and anti-inflammatory cytokine and chemokine production in a mouse experimental autoimmune encephalomyelitis (EAE) model. Nox2 deficiency attenuates EAE-induced neural damage and reduces disease severity, pathogenic immune cells infiltration, demyelination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…On the other hand, the nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase (Nox2) is highly expressed by professional phagocytes, including microglia, and is essential for the activation of these cells. Upon Nox2 activation, microglia increase the chemotaxis of peripheral pathogenic immune cells into the CNS, causing demyelination and axonal damage (Hu et al, 2021). Although this latter study could benefit from a cell-specific KO strategy to investigate Nox2 in microglia, authors clearly show that Nox2-deficient mice display less inflammatory infiltrates and demyelination, as well as that microglia-mediated expression of the pool of cytokines and chemokines, is substantially decreased (Hu et al, 2021).…”
Section: Microglia In Progressive Multiple Sclerosismentioning
confidence: 95%
“…On the other hand, the nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase (Nox2) is highly expressed by professional phagocytes, including microglia, and is essential for the activation of these cells. Upon Nox2 activation, microglia increase the chemotaxis of peripheral pathogenic immune cells into the CNS, causing demyelination and axonal damage (Hu et al, 2021). Although this latter study could benefit from a cell-specific KO strategy to investigate Nox2 in microglia, authors clearly show that Nox2-deficient mice display less inflammatory infiltrates and demyelination, as well as that microglia-mediated expression of the pool of cytokines and chemokines, is substantially decreased (Hu et al, 2021).…”
Section: Microglia In Progressive Multiple Sclerosismentioning
confidence: 95%
“…When Ncf1 gene or genes of other significant components of NOX2 complex are disrupted, NOX2 complex losses the ability to produce ROS ( 11 ). The local inflammatory responses of NOX2 vary in different organs and different stimulations ( 31 , 32 ). In this study, we focused on NOX2 regulation of joint inflammation (a local inflammation).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte and microglial infiltration in the CNS was also significantly decreased compared to heterozygous and wild-type controls. Interestingly, the authors showed that only immune infiltration in the CNS is reduced, as immune cell populations in peripheral tissues such as the spleen and cervical lymph node are similar in NOX2 -/- and wild-type mice post EAE induction ( 100 ). Microglial activation was also decreased in NOX2 -/- mice, with inflammatory cytokine and chemokine secretion levels in the CNS also decreased.…”
Section: Reactive Oxygen Species In the Cnsmentioning
confidence: 99%